Kekerasan Dalam Rumah Tangga (KDRT) Terhadap Perempuan Dalam Perspektif Pekerjaan Sosial - Ani Kartika; Asep Suherman (CV. ITTC INDONESIA, 2024)
National Commission on violence against women (2015) noted that violence against women showed a widespread pattern. The 2016 annual press release (Catahu) released that there were 321,752 of violence cases. The largest type of violence against women was violence in the personal sector. Violence in the form of rape was 72% (2,399 of cases), violence in the form of obscenity was 18% (601 of cases), and sexual abuse was 5% (166 of cases). The majority of personal violence victims (domestic / household) were women. The forms of domestic violence included physical violence, psychological violence, sexual violence and neglect of the household; while the main factor was the lack of communication and disharmony among family members. The impact in the short term was usually like a physical injury, disability, pregnancy, loss of work, and so forth; while the long-term effects werepsychological disorders (psychiatric), loss of confidence, fend for oneself, trauma and appearance of fear to depression. The handling of domestic violence is one of the focuses of social workers to play a role in helping / assisting the recovery of victims. The social worker should be able to convince the victims to dare to express their problems, to give a sense of security, and comfort. Social workers in helping victims of domestic violence should have knowledge and alignment to the victims that the slightest violence is a form of crime against humanity. Victims of domestic violence must immediately obtain the protection, security assurance and social assistance. The efforts which can be done by social workers are counseling and family counseling. Those are done as a form of therapy so that victims do not feel the prolonged trauma and they can think calmly.